URGENSI PEMBENTUKAN UNDANG-UNDANG TENTANG PENGHINAAN DALAM PERSIDANGAN (CONTEMPT OF COURT) UNTUK MENEGAKKAN MARTABAT DAN WIBAWA PERADILAN - Sareh Wiyono M (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
The law of contempt of court must be formed immediately along with the restriction of which action becomes part of contempt in the court or which one doesn’t. The judge must improve the professionalism and self-Integrity in running the duty and obligationKeywords : Urgency, Contempt, Court